Practical optimization of liquid chromatography/mass spectrometry conditions and pretreatment methods toward the sensitive quantification of auxin in plants. (19th February 2020) - Sugahara, Kohtaro; Kitao, Kazunori; Yamagaki, Tohru; Koyama, Tomotsugu
Abstract : Rationale: The plant hormone auxin, indole‐3‐acetic acid, regulates many aspects of plant growth and development. Auxin quantification should offer broad insights into its mechanistic action in plants. However, limited auxin content in plant tissues hampers the establishment of quantification methods without the highest graded instruments or deeply specialized experimental techniques. Methods: In this study, we detailed optimized conditions for high‐performance liquid chromatography coupled with triple‐quadrupole mass spectrometry (LC/MS). We compared LC/MS conditions, such as columns, mobile phases, parameters of acquisition methods (selective or multiple ion monitoring), dwell times (DTs), and channel numbers, using differentially mixed authentic auxin and its related compounds. We further investigated pretreatment methods through the optimization of auxin recovery and irrelative compound removal from plant tissues prior to the LC/MS analysis. Results: Our LC/MS analysis demonstrated the particular importance of the column, DTs, and channel numbers on detection sensitivity. Our comparative analysis developed optimal pretreatment methods, including the pulverization of plants, concentration of extract through centrifugal evaporation, and removal of irrelative metabolites using liquid–liquid extraction and a spin filter. We injected plant samples into our LC/MS system, quantified auxin and eight related compounds in a single measurement, and determined the auxin increase in an auxin over‐producing mutant. Conclusions: Our practical optimization of LC/MS conditions and pretreatment methods provides detailed experimental processes toward the sensitive quantification of auxin from 10 mg of plant tissue. These processes have not always been clearly documented; therefore, our protocol could broadly contribute to technical advances in plant growth and development research.